SUSTAINABLE DEVELOPMENT OF ENTREPRENEURSHIP IN AGRICULTURAL MANAGEMENT AND FOREIGN EXPERIENCES - Rakhimov Azizbek Saliyevich (Web of Journals Publishing, 2025)
The article describes the achievements and disadvantages in the process of managing the agricultural sector based on innovative technologies and foreign experience in this area.
Keywords: Agro-industrial complex, innovative development, innovative news, competitiveness in the world market, agricultural innovation complex, modern agro-innovative complex, modern agro-innovative complex, innovation minijack.